Reanimating the strangled rivers of Aotearoa New Zealand - Brierley, Gary J.; Hikuroa, Daniel; Fuller, Ian C.; Tunnicliffe, Jon; Allen, Kristiann; Brasington, James; Friedrich, Heide; Hoyle, Jo; Measures, Richard (WIREs Water, 2022)
Contemporary management practices have artificially confined (strangled) river systems in Aotearoa New Zealand to support intensified land use in riparian areas. These practices work against nature, diminishing the functionality and biodiversity values of living rivers, and associated socio-cultural relations with rivers. River confinement can accentuate flood risk by promoting development in vulnerable locations and limiting the flexibility to adapt to changing climate, prospectively accentuating future disasters. To date, uptake of space-to-move management interventions that seek to address such shortcomings is yet to happen in Aotearoa New Zealand. This is despite the fact that such practices directly align with Māori (indigenous) conceptualizations of rivers as indivisible, living entities. Treaty of Waitangi obligations that assert Māori rights alongside colonial rights of a settler society provide an additional driver for uptake of space-to-move initiatives. This article outlines a biophysical prioritization framework to support the development and roll out of space-to-move interventions in ways that work with the character, behavior, condition, and evolutionary trajectory (recovery potential) of each river system in Aotearoa. This article is categorized under: Water and Life > Conservation, Management, and Awareness Science of Water > Water and Environmental Change
Keywords: environment; environmental protection; mana moana; mana tupuna; mana whenua; mātauranga māori; tikanga | indigenous law; water management

Navigating towards marine co-management with Indigenous communities on-board the Waka-Taurua - Maxwell, Kimberley H.; Ratana, Kelly; Davies, Kathryn K.; Taiapa, Caine; Awatere, Shaun (Marine Policy, 2020)
Developing equitable marine management systems that recognise Indigenous worldviews, values, and practices, alongside international initiatives such as Ecosystem-Based Management (EBM) are paramount in countries which aim to recognise Indigenous rights. This is the case for New Zealand (NZ) where Indigenous-Māori rights to partner with the Government for the purpose of environmental management were guaranteed under the Treaty of Waitangi, 1840, and subsequent Acts (e.g. Resource Management Act, 1991). Our aim was to explore how both Indigenous-Māori and NZ societal values can be integrated into a marine co-management decision-making framework. Here we describe the Waka-Taurua (double-canoe) framework, and how it can be applied in developing a NZ marine management system (NZ-MMS), which includes both kaitiakitanga (a Māori concept of reciprocal care between Indigenous-Māori people and their territorial environment), and EBM, equitably. We argue that the Waka-Taurua framework can improve how marine co-management systems are developed by facilitating a more structured and equitable discussion of both Indigenous-Māori and broader societal worldviews, values, and practices.
Keywords: environmental management; governance; kaitiakitanga; kāwanatanga; water management

Using mātauranga Māori to inform freshwater management - Harmsworth, Garth; Awatere, S.; Pauling, C. (Landcare Research Policy Brief, 2013)
Keywords: co-governance; environment; governance; hapū; iwi; kāwanatanga; local government; water management

Integrating Indigenous Knowledge and Freshwater Management: An Aotearoa/New Zealand Case Study - Hudson, Maui; Watene-Rawiri, Erina; Robb, Mahuru; Collier, Kevin; Awatere, Shaun; Harmsworth, Garth; Henry, Jacqueline; Quinn, John; Death, Russell; Hamilton, David; Maru, John (The International Journal of Science in Society, 2016)
Keywords: governance; iwi; kāwanatanga; local government; treaty settlements; water management

Indigenous Māori values and perspectives to inform freshwater management in Aotearoa-New Zealand - Harmsworth, Garth; Awatere, Shaun; Robb, Mahuru (Ecology and Society, 2016)
In response to widespread water quality and quantity issues, the New Zealand Government has recently embarked on a number of comprehensive freshwater management reforms, developing a raft of national discussion and policy documents such as "Freshwater Reform 2013 and Beyond" and a National Policy Statement for freshwater management (NPS-FM 2014). Recent resource management reforms and amendments (RMA 2014), based on previous overarching resource management legislation (RMA 1991), set out a new approach and pathway to manage freshwater nationwide. Internationally, there is an increasing trend to engage with indigenous communities for research and collaboration, including indigenous groups as active participants in resource management decision making. What is driving this change toward more engagement and collaboration with indigenous communities is different for each country, and we document the progress and innovation made in this area in New Zealand. The indigenous rights of Māori in New Zealand are stated in the 1840 Treaty of Waitangi and in many forms of New Zealand's legislation. Local and central governments are eager to include local indigenous Māori groups (iwi/hapū) in freshwater management planning processes through meaningful engagement and collaboration. Key to the success of collaborative planning processes for Māori are enduring relationships between local government and Māori, along with adequate resourcing for all partners contributing to the collaborative process. A large number of shared governance and management models for natural resource management have emerged in New Zealand over the past 20 years, and some recent examples are reviewed. We provide some discussion to improve understanding and use of the terms used in these management models such as cogovernance, comanagement, and coplanning, and describe some of the more important frameworks and tools being developed with Māori groups (e.g., iwi/hapū), to strengthen Māori capacity in freshwater management and to support good collaborative process and planning.
Keywords: co-governance; environment; hapū; iwi; kāwanatanga; local government; mātauranga māori; resource management; tikanga | indigenous law; tiriti o waitangi/treaty of waitangi; water management

From hydrology to policy development and implementation: Trends in Aotearoa New Zealand's freshwater management and governance - Fenemor, Andrew; Kirk, Nicholas; Harmsworth, Garth; Taylor, Lara; Weir, Julian; Robson, -Williams Melissa (Journal of Hydrology (New Zealand), 2021)
This section reviews changes to water management and governance in the past ten years. We open with a summary of Aotearoa New Zealand's historical legislative context in regard to rivers, catchments and freshwater resources. We describe the roles of local government, Maori and central government. We detail the growing recognition of tangata whenua values in water management alongside belated development of national policy direction on water quality and allocation. Drawing on the description of modelling advances, we summarise how models are being used in contemporary water management. Finally, we review the implementation of freshwater policy and the integration of science and water policy. In concluding, we argue that integration and implementation challenges must be addressed as hydrologists look beyond 2021 towards future significant legislative changes affecting water and catchment management nationwide.
Keywords: environmental management; policy making; water management

Where to for collaboration in land and water policy development in Aotearoa New Zealand? Guidance for authorising agencies - Kirk, Nicholas; Robson-Williams, Melissa; Bammer, Gabriele; Foote, Jeff; Butcher, Lian; Deans, Neil; Harmsworth, Garth; Hepi, Maria; Lilburne, Linda; Nicholas, Barbara; Small, Bruce; Turner, James A.; et al. (Kōtuitui: New Zealand Journal of Social Sciences Online, 2022)
For the past decade, collaboration has been the preferred method of devising land and water policy in Aotearoa New Zealand to achieve agreed outcomes. However, the use of collaboration in policymaking is at a crossroads, as some argue it is unrealistic to expect stakeholders and tangata whenua with competing interests to work in partnership on contentious policy issues. To help clarify the future direction of collaboration, this paper provides authorising agencies (those with responsibility for the policy problems) with prompts to reflect ex ante on the advantages and disadvantages of pursuing collaboration. Based on a retrospective review of collaborations in New Zealand’s land and water policymaking, and a two-day symposium with collaboration practitioners, we identify situations that are potentially less suited to collaboration owing to factors that are challenging to overcome through process design. Four issues that affect the success of collaborations are identified: the nature of the policy problem, the personal and collective qualities of those involved, power relationships, and the collaborative process. Finally, we draw together practical lessons from history, the symposium, and the literature to develop a list of questions for authorising agencies to use to reflect on the advantages and disadvantages of pursuing collaboration.
Keywords: co-governance; land policy; policy; water management